Caracterização das variações de tensão de curta duração e seus impactos em uma planta da indústria alimentícia - Reinaldo Moreira Maia (2011)
The Short-Duration Voltage Variations (SDVV) can generate great prejudice to industries that possesses installed equipments that are sensitive to these phenomena. In this work the characteristics of the SDVV will be presented as well as a case study on the behavior of some equipments of a food industry when submitted to SDVV, describing the effects and prejudices caused by it. The methodology of the work consisted in monitoring the industry characteristics for 4 years, period in which the characteristics of the disturbs in the power supply network and the consequences over the internal productive processes were evaluated. Laboratory tests were used to identify the sensitivity of some industrial equipments submitted to SDVV. With the measurements and tests results it was determined the SDVV sensitivity of the industry's connection point and the sensitivity and susceptibility of some equipments that were installed in its industrial plant. The knowledge on the sensitivity of the equipments allowed an increase in the robustness of the plant through the desensitization of the undervoltage protection, the utilization of uninterrupted sources of energy in more sensitive charges and the modification of the main Programmable Logic Controller (PLC) algorithm, therefore reducing the number of disturbs that impacted the behavior of the plant by 94,7%. The work allowed a larger knowledge on the behavior of command and control equipments used in the process, helping future specifications for device replacement. Besides, in this work, it was intended to assemble a group of procedures capable of being replicated in similar industrial processes